Judgement, decision making and success in sport - Bar-Eli, Michael (W-B series in sport and exercise psychology ;, 2011)
"Judgment, Decision-Making and Success in Sport presents a thorough overview and assessment of the study of Judgment and Decision-Making (JDM) in sports psychology, and represents an important source of information for those interested in the possible causes and reasons for success and failure in sport ... The only book to apply the principles of JDM to sport. Applies theory to practice by looking at problems of athletes, coaches, and referees and providing recommendations for dealing with them. Offers an overview of current JDM research. Useful for psychologists, physical education teachers, sports scientists, and researchers in this field."--